Review Sistematik: Analisis Kualitas Produk Kaki Pallet Menggunakan Basic Seven Tools - Donny A. Ferdiansyah; Agustian Suseno; Ari Teguh Septiansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Over time, the development of business in Indonesia is quite fast. However, the competition in the world of work is getting tougher. A company will compete to find a method to win a competition, one of which is to put the company's focus on the quality of the product produced. In order to maintain the consistency of the quality of the products produced in accordance with the demands of market needs, it is necessary to carry out quality control or quality control over the process activities undertaken. The criteria used in writing this article are (1) to describe the analysis of product quality, (2) to be written in Indonesian, (3) to have complete sections, and (4) to be published in the range of 2017 – 2022. The basic seven tools method is used. to control the quality of the resulting product. Control and supervision are activities carried out to ensure that production and operating activities are carried out in accordance with what is planned and if there are deviations, these deviations can be corrected so that what is expected can be achieved